Values of Megibung Tradition in Tumbu Traditional Village, Karangasem, Bali: An Ethnopedagogical Study - Ni Putu Ari Krisnayanthi Subyanto; I Wayan Rasna (Jurnal Pendidikan dan Pengajaran, 2022)
Bali is known for its culture and customs, one of which is the culture of "eating together" activities or what is known as "mengibung." This research will explore the value side of the megibung tradition, which is still found in the rules of the people of Tumbu Village. This study aims to analyze the values ​​in the Megibung practice in the Traditional Village of Tumbu Karangasem. This type of research is qualitative research. The data collection techniques used consisted of observation, interviews, and documentation. The method used to analyze the data is descriptive qualitative analysis. The results of the research are that the megibung tradition contains values ​​consisting of the first philosophical values in the megibung practice. It teaches us to instill a sense of togetherness, cooperation, justice, and ethics in society. In the megibung tradition, both social values teach us to have a sense of kinship, tolerance, and cooperation in culture. We are taught the three religious matters always to be grateful to God Almighty and our ancestors for what has been given. The megibung tradition can increase character values ​​in students.